Isolation of citronellal from Cymbopogon nardus (L) Rendle and its activity test as a burn healing in mice - Yelfi Anwar; Novia Aditia Ningtiyas; Partomuan Simanjuntak (Current Research on Bioscences and Biotechnology, 2020)
Citronellal is one of the main compounds of essential oils of Cymbopogon nardus (L) Rendle, which is the most important chemical compound in the cosmetics and pharmacy industry. This study aimed to isolate the citronellal from the essential oil of Cymbopogon nardus (L) Rendle and activity on burns in male white mice (Mus musculus (L). The isolation method used column chromatography and n-hexane-ethyl acetate as eluent (20 : 1). The isolate obtained was used to burn activity on the back of male white mice (Mus musculus (L)). The ointment formula 0.25%, 0.5% and 1% were prepared using vaseline flavum. Based on the test using thin layer chromatography with the addition of cerium sulphate as a spotting appearance, was given one spot in the 4th isolate. Based on characterization data by UV-Vis spectrum, FTIR spectrum and GC-MS chromatogram showed that F4 isolate was citronellal. Based on the results of the burn activity on all concentrations, formula 1% showed the best burn healing activity. Citronellal can be isolated from the essential oil of Cymbopogon nardus (L) Rendle and has healing activities for burns in male white mice.